Homomorphisms of Approximation Spaces. (13th May 2012) - Wang, Zhaohao; Shu, Lan; Ding, Xiuyong
Abstract : The notion of the homomorphism of approximation spaces is introduced. Some properties of homomorphism are investigated, and some characterizations of homomorphism are given. Furthermore, the notion of approximation subspace of approximation spaces is introduced. The relations between approximation subspaces and homomorphisms are studied.